Implementasi Kebijakan Program Chromebook untuk Guru di Kecamatan Binawidya, Kota Pekanbaru - Rizka Ramadani; Weni Puji Hastuti (Al-Manar Journal of Public Administration and Management, 2025)
The purpose of this study was to determine the implementation of the chromebook program in binawidya sub-district in pekanbaru city. This research uses a qualitative approach with data collocted through interviews, observations, and documentation. The results of the study indicate that the implementation of the chromebook program policy can be said to be good when seen from the students’ response to the use of chromebook, namely the enthusiasm of students who can provide new and enjoyable learning experiences so that they can create active learning that leads to increased interest and motivation in learning, with the use of chromebooks students can master and understand learning. Teachers have used most of the applications available on chromebooks in their learning.